Contrasting Hydrological Controls on Bed Properties During the Acceleration of Pine Island Glacier, West Antarctica. Issue 1 (17th January 2019) - Bougamont, M.; Christoffersen, P.; Nias, I.; Vaughan, D. G.; Smith, A. M.; Brisbourne, A.
Abstract: In the Amundsen sector of West Antarctica, the flow of glaciers accelerates when intrusion of warm ocean water onto the continental shelf induces strong melting beneath ice shelves and thinning near the glaciers' grounding line. Predicting the future of these glaciers is, however, hindered by a poor understanding of the dynamical processes that may exacerbate, or on the contrary modulate, the inland ice sheet response. This study seeks to investigate processes occurring at the base of Pine Island Glacier through numerical inversions of surface velocities observed in 1996 and 2014, a period of time during which the glacier accelerated significantly. The outputs show that substantial changes took place in the basal environment, which we interpret with models of undrained subglacial till and hydrological routing. The annual basal melt production increased by 25% on average. Basal drag weakened by 15% over nearly two thirds of the region of accelerated flow, largely due to the direct assimilation of locally produced basal meltwater into the underlying subglacial sediment. In contrast, regions of increased drag are found to follow several of the glacier's shear margins and furthermore to coincide with inferred hydrological pathways. We interpret this basal strengthening as signature of an efficient hydrological system, where low‐pressure water channels have reduced the surrounding basal water pressure. These are the first identified stabilization mechanisms to have developed alongside Pine Island ice flow acceleration. Indeed, these processes could become more significant with increased meltwater availability and may limit the glacier's response to perturbation near its grounding line. Key Points: Numerical inversions interpreted with undrained till and water routing models are used to infer basal changes and hydrological conditions Weaker beds in central troughs are offset by stronger beds along shear margins, which coincide with major hydrological pathways The future flow of PIG may depend on the coevolution of basal properties and shear margins in addition to its interaction with the ocean